Acute pancreatitis complicating choledochal cysts in children. (4th October 2016) - Muthucumaru, Mathievathaniy; Ljuhar, Damir; Panabokke, Gayathri; Paul, Eldho; Nataraja, Ramesh; Ferguson, Peter; Dagia, Charuta; Clarnette, Tom; King, Sebastian
Abstract : Aim: To analyse the characteristics of patients with choledochal cysts presenting with acute pancreatitis. Methods: Multicenter retrospective review of all paediatric patients (<18 years) with choledochal cysts managed over a 14‐year period (2001–2014) at two tertiary paediatric surgical centres. Patient data were analysed for demographics, presentation, radiological classification of cyst type (Todani), operative interventions, complications and long‐term follow‐up. Results: A total of 49 patients with choledochal cysts were identified with 15 (31%) being Type I fusiform, 18 (37%) Type I cystic and 16 (32%) Type IV‐A. Seventeen (35%) patients presented with acute pancreatitis, one having had an ante‐natally diagnosed choledochal cyst. Patients presenting with pancreatitis were older when compared to the non‐pancreatitis group (5.1 vs. 1.2 years, P = 0.005). Nine out of 16 (53%) patients with Type IV‐A cysts presented with pancreatitis compared to five (33%) of Type I fusiform and three (17%) of Type I cystic. There was however no statistically significant association between Todani types and the development of pancreatitis (Type I fusiform, P = 1.0; Type I cystic, P = 0.063; Type IV‐A, P = 0.053). The rate of complications was similar in both groups. Conclusion: Pancreatitis was a common presentation in children with a choledochal cyst, however, there was no clear statistically significant association with Todani types and pancreatitis.